Prevalence and associated factors of caesarean section in Addis Ababa hospitals, Ethiopia - Tsegaye, Hiwot; Desalegne, Birehanu; Wassihun, Biresaw; Bante, Agegnehu; fikadu, kassahun; Debalkie, Megbaru; Yeheyis, Tomas (The Pan African medical journal, 2019)
Caesarean section refers to the operation of delivering a baby through incisions made in the mother's abdominal wall and uterus. A caesarean section is medically indicated when a significant risk of adverse outcome for mother or baby is present. The objective of this study was to assess the prevalence and associated factors of caesarean section in Addis Ababa Hospitals, Ethiopia. Institutional based cross-sectional study design was employed on 298 women from between April and May 2017. Study subjects were selected using systematic random sampling by considering the number of delivery. A structured questionnaire was used to collect the data. The data were coded and entered into Epi data version 3.1 and the analysis was carried out in a statistical package for social science versions 22. Descriptive statistics for each variable and binary logistic regression analysis with 95% CI was carried out. A total of 298 mothers were participated in the study with a response rate of 100%. The overall prevalence of caesarean section in this study was 38.3%. The multivariable analysis indicated that mother who had collage and above [AOR = 3.46 (95%CI; 1.2, 10.76)], giving birth in private health facility [AOR = 1.48 (95%CI; 1.84, 2.59)], and having risk factors [AOR = 2.86 (95%CI; 1.96, 3.42)], were some of the factors associated with caesarean section. The finding of this study showed that the prevalence of caesarean section was higher in women who gave birth in private health facility, mothers having risk factors, and mothers having educational status of diploma and above. Therefore, identifying risky group during antenatal care follow-up and restraining numbers of caesarean section in private health facilities is essential steps to reduce high prevalence of caesarean section.